Estudio de rentabilidad del cultivo de estevia (stevia rebaudiana bertoni) en Trujillo, La Libertad - Cueva Chávez, Víctor Antonio (2016)
Stevia rebaudiana Bertoni. (Stevia) is a semi-evergreen shrubby plant, native to northeastern Paraguay, belonging to the family of composite. Its economic importance is that, in its leaves, has a substance called stevioside, consisting of a mixture of at least six diterpene glycosides, which is 100-400 times sweeter than sucrose and by their physico-chemical characteristics and toxicological allows inclusion in the human diet to be used as a natural dietary sweetener, without side effects. The need to include in our diet and the ability to export has increased interest in this species by the producers. Naturally it spreads achenes, but the low cultural value of seeds (10 to 15%) and the heterogeneity of the resulting populations indicate the need to develop and / or adjust alternatives, simple and inexpensive techniques that allow the massive propagation of genotypes selected. The aim of this work is to study the profitability of the crop, for which we have requested information from the company STEVIA COLONEL SA in order to evaluate the biological adaptability and profitability of stevia for commercial promotion in the town of Trujillo, La Libertad.